2013
DOI: 10.5539/ijbm.v8n12p1
|View full text |Cite
|
Sign up to set email alerts
|

CEO Compensation in Canada, 1971-2008

Abstract: This paper draws from a unique database spanning over 35 years of Canadian CEOs' compensation to explore the interplay among: the information available to boards of directors of Canadian companies for making executive pay decisions, the Canadian business environment, and the compensation that Canadian CEOs received. We find a very strong correlation between Canadian CEOs' compensation and the amount of information on CEO compensation available to boards of directors. We further note that the evolution of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Canadian research on the determinants of CEO compensation is relatively sparse, with most of the more recent research focusing on CEO compensation and firm governance and corporate social responsibility (Bodolica & Spraggon, 2009;Craighead, Magnan, & Thorne, 2004;Park, Nelson, & Torabzadeh, 2000), as well as strategy and pay structure (see for example Chourou, Abaoubb, & Saadi, 2008;Gélinas & Baillargeon, 2013). Only a few studies examine the relationship between firm size, performance, and CEO compensation (see Nulla, 2013;Singh & Agarwal, 2002).…”
Section: Research On Executive Compensation In Canadamentioning
confidence: 99%
See 2 more Smart Citations
“…Canadian research on the determinants of CEO compensation is relatively sparse, with most of the more recent research focusing on CEO compensation and firm governance and corporate social responsibility (Bodolica & Spraggon, 2009;Craighead, Magnan, & Thorne, 2004;Park, Nelson, & Torabzadeh, 2000), as well as strategy and pay structure (see for example Chourou, Abaoubb, & Saadi, 2008;Gélinas & Baillargeon, 2013). Only a few studies examine the relationship between firm size, performance, and CEO compensation (see Nulla, 2013;Singh & Agarwal, 2002).…”
Section: Research On Executive Compensation In Canadamentioning
confidence: 99%
“…Only a few studies examine the relationship between firm size, performance, and CEO compensation (see Nulla, 2013;Singh & Agarwal, 2002). Gélinas and Baillargeon (2013) analyzed data in the annual Canadian executive compensation survey of a large consulting firm from 1971 to 2008. They found strong relationships between Canadian CEOs' compensation and the amount of information on CEO compensation available to boards of directors.…”
Section: Research On Executive Compensation In Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…A sixfold increase in top executives' salaries in the US over a period of more than 20 years is linked to globalization, greater risk and firm size (Gabaix & Landier, 2008). Over a period of 35 years , the rise in executive compensation in Canada has been closely related to the amount of information made available to members of the board (Gélinas & Baillargeon, 2013). This trend intensified as of 1994, the year in which information on executive pay was made publicly available (Craighead et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 90%
“…For instance, studies have shown that executive pay levels continue to rise (Murphy, 2012;Gabaix & Landier, 2008;Gélinas & Baillargeon, 2013;Craighead, Magnan, & Thorne, 2004) and that such increases are not always performance-related (Bebchuk & Fried, 2005). At the time of the financial crisis in 2007, public opinion as a whole considered executive compensation figures to be unacceptable because they were unrelated to firms' actual performance.…”
Section: Introductionmentioning
confidence: 99%